SEBOROIC DERMATITIS IN CHILDREN WITH HYDROCEPHALUS AND MALNUTRITION: HOW IS THE CORRELATION ? - Sintya Dwi Cahyani; Dedianto Hidajat (Unram Medical Journal, 2022)
Abstract Seborrheic dermatitis is a chronic recurrent inflammation of the skin that manifests as well-defined erythematous macules or plaques with oily yellow-white scales accompanied by pruritus. This condition usually occurs as an inflammatory response to Malassezia species and tends to occur in areas with a large number of sebaceous glands. Seborrheic dermatitis in children often occurs on the scalp, eyebrows, skin behind the ears, diaper area, skin folds on the neck and under the arms. Various intrinsic and environmental factors, such as sebaceous gland secretion, skin fungal colonization and individual susceptibility all contribute to the pathogenesis of seborrheic dermatitis. We discuss a case of a 5 year old child with clinical hydrocephalus and poor nutrition accompanied by complaints of dandruff with a yellowish color that is intermittent. Initially, a red patch was seen on the patient's left nape which gradually spread to both sides. After 1-2 days the redness becomes yellowish and brittle dandruff. These complaints began to arise when the patient's head was getting bigger so that the patient seemed difficult to move his head. Description of the lesion on the back of the scalp to the folds of the neck in the form of solitary erythematous macular lesions, plaque-shaped, well-defined, irregular, regionally distributed in the posterior cervical region, accompanied by thin yellowish and oily scales. The patient was diagnosed with seborrheic dermatitis. It is important to know the risk factors and management in cases of seborrheic dermatitis to prevent recurrence. Kata kunci : Seborrheic dermatitis, malnutrition, immunocompromised